2013
DOI: 10.3390/atmos4040472
|View full text |Cite
|
Sign up to set email alerts
|

Total Gaseous Mercury Concentration Measurements at Fort McMurray, Alberta, Canada

Abstract: . Principal component analysis also shows that the highest TGM concentrations observed are a result of forest fire smoke near the monitoring station. Back trajectory analysis highlights the importance of long-range transport, indicating that unseasonably high TGM concentrations are generally associated with air from the southeast and west, while unseasonably low TGM concentrations are a result of arctic air moving over the monitoring station. In general, TGM concentration appears to be driven by diel and seaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…All papers reported differences between the subsets and between the full data set and the subsets to some extent (Gao, 2007;Parsons et al, 2013, Xu et al, 2014. In the 2007-2011 Windsor, Ontario, TGM study (Xu et al, 2014), seasonal PCA revealed that the transport component seems to be very influential to TGM concentrations due to high winds.…”
Section: Pca Results From Data Subsetsmentioning
confidence: 99%
See 4 more Smart Citations
“…All papers reported differences between the subsets and between the full data set and the subsets to some extent (Gao, 2007;Parsons et al, 2013, Xu et al, 2014. In the 2007-2011 Windsor, Ontario, TGM study (Xu et al, 2014), seasonal PCA revealed that the transport component seems to be very influential to TGM concentrations due to high winds.…”
Section: Pca Results From Data Subsetsmentioning
confidence: 99%
“…Similarly, TGM data collected in Fort McMurray, Alberta, were stratified into three concentration ranges and then each data subset were analyzed separately using PCA (Parsons et al, 2013). For the full data set, TGM variability was primarily attributed to diurnal variability followed by forest fire smoke, temperature and snow depth, industrial sulfur, and combustion processes.…”
Section: Pca Results From Data Subsetsmentioning
confidence: 99%
See 3 more Smart Citations